Analysis of the Loan Program of the Savings and Loan Business Unit at BUMDesa Mutiara Welirang, Ketapanrame Village According to the Perspective of Sharia Economics - Ibad, Muhamad Sobarul (Malacca: Journal of Management and Business Development, 2024)
Village development through Village-Owned Enterprises (BUMDes) is an important strategy to improve community welfare by empowering local economic potential. BUMDes, is a legal entity owned and managed by the village community. One example is BUMDesa Mutiara Welirang in Ketapanrame Village, Mojokerto, which manages various business units including savings and loans. This savings and loans unit applies the sharia concept with the qardh contract, providing interest-free loans to help people establish businesses or obtain capital, demonstrating BUMDes' commitment to supporting the village economy sustainably and following Islamic economic principles. So, the formulation of the problem in this study, first: How is the implementation of the Savings and Loans Business Unit loan program at BUMDesa Mutiara Welirang, Ketapanrame Village? Second: What are the results of the analysis of the BUMDesa Mutiara Welirang Savings and Loans Business Unit loan program from a Sharia Economic perspective? Third: How is Risk Management in the Savings and Loans Business Unit at BUMDesa Mutiara Welirang, Ketapanrame Village? The research method used is qualitative descriptive with a case study approach. Data collection was conducted through field observations, in-depth interviews with tourism managers, community leaders, and tourists, and analysis of related documents. The results of this study indicate that: first, the BUMDes savings and loan business unit loan program has become an effective financing alternative at the village level, increasing financial inclusion through easy access and simple procedures using the infaq system. Second, the Mutiara Welirang BUMDesa Savings and Loan Business Unit applies Sharia economic principles through the infaq and qardh mechanisms in its loan program. Third, the Mutiara Welirang BUMDesa Savings and Loan Business Unit has implemented comprehensive risk management, covering aspects of operational, liquidity, and credit risk.